Soil Health Data Acquisition System with Augmented Reality (AR) Features: Innovation in Sustainable Plantation Management - Sarosa Castrena Abadi; Siti Aminah; Cepi Ramdani (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Plantations in West Java are vital to Indonesia’s agricultural economy, yet they face significant challenges in efficient and real-time soil monitoring due to reliance on conventional, labor-intensive methods. This study aims to develop a distributed soil health data acquisition system integrated with Augmented Reality (AR) visualization to enable intuitive, real-time access to key soil parameters specifically moisture, pH, and NPK (Nitrogen, Phosphorus, Potassium) levels without manual sampling. The system employs a multi-hop LoRa-based wireless sensor network comprising two sensor nodes and a master gateway. Node 2 collects soil nutrient data and relays it to Node 1, which aggregates it with environmental data before forwarding the payload to the gateway. The gateway publishes the consolidated data to an MQTT broker, which feeds both a Firebase database and a Unity-based AR application. System performance was evaluated through field tests measuring latency, packet loss, and AR rendering accuracy across ten data batches. The system achieved stable communication with an average end-to-end latency of 3.00–3.40 ms and successfully visualized soil metrics in real time through the AR interface. Although minor packet loss (up to 20%) occurred in later test batches, data integrity remained sufficient for monitoring non-rapidly changing soil conditions. The integration of LoRa multi-hop communication and AR provides a robust, scalable framework for real-time soil monitoring, offering a practical foundation for future smart agriculture systems in plantation environments.